Ecological-Economic Zoning as an Instrument for the Protection of Water Source Areas: A Case Study in Brazil - Ribas, Luiz César; Sarmiento , Miguel Angel; Robusti, Eliane Araújo; Duarte, João Paulo Pereira (Scientific Journal ANAP, 2025)
Objective - This study aims to analyze the Ecological-Economic Zoning (ZEE) proposed by the municipality of Botucatu-SP, according to Law No. 6,599/2024, focusing on the environmental protection of water sources. The analysis considers the different zoning categories established and their impacts on the studied territory.Methodology - An exploratory study was conducted with a documentary, bibliographic, and qualitative approach. The study used a case study method, focusing on a territory located in the Alto Pardo river basin, analyzing the ZEE guidelines for different types of zones (rural, specific urbanization, and rurban).Originality/Relevance - This study contributes to the discussion on environmental zoning and its relationship with sustainability, addressing a specific model applied at the municipal level. It highlights the analysis of Botucatu’s ZEE, offering insights into how territorial planning instruments can help in water source protection and sustainable land management.Results - Botucatu’s ZEE classified the territory into different zones, establishing guidelines for rural and urban development. The study identified two main aspects:• Maintaining sustainable characteristics in low-density areas, encouraging non-residential activities such as tourism and organic farming.• Environmental and urban regularization in neighborhoods undergoing adaptation processes, such as Demetria and Roseira.Theoretical/Methodological Contributions - The research reinforces the importance of ZEE as a territorial planning tool, highlighting its impact on the integrated management of environmental and urban policies. The study contributes to the literature by discussing the criteria and parameters adopted in zoning, as well as providing a practical example of environmental legislation application.Social and Environmental Contributions - The proposed ZEE provides guidelines for environmental sustainability and water source protection, promoting appropriate land use. It also supports the regularization of urban and rural areas, ensuring a better quality of life for the population and encouraging sustainable activities.KEYWORDS: Sustainable Regional Development. Environmental Policies. Public Policies. Environmental Protection
Keywords: Sustainable Regional Development; Environmental Policies; Public Policies; Environmental Protection of Water Source Area